BILATERAL INVESTMENT TREATIES REPUBLIC OF KAZAKHSTAN WITH FOREIGN STATES - Kasim Syrbaevich, Мауленов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The investment policy of the Republic of Kazakhstan is a system of measures of the legislative, executive and controlling character taken by authorized governmental bodies for the purpose of increasing the investment activity of business entities. As for the investment aspect, Kazakhstan currently remains one of the most attractive countries with prospects for future of the CIS states. Formation of a democratic, temporal, legal and social state envisages, in particular, perfection of state administrative relations and their legal regulation, putting the status of participants of these relations in accordance with new tasks confronting